The Influence of Transformational Leadership and Organizational Culture on Work Productivity - Rohidin, Rohidin; Saepudin, Saepudin; Juliana, Juliana; Tjahjono, Budi; Suryahim, Iim (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to determine and analyze the influence of transformational leadership and organizational culture on the productivity of lecturers at the Laa Roiba Bogor National Islamic Institute. This research uses quantitative research methods with survey techniques to answer the hypothesis tests that have been formulated. Respondents totaled 160 lecturers, and the sampling technique used was random. The transformational leadership, organizational culture, and work productivity questionnaires were validated using the product moment correlation formula; Reliability is measured using the Cronbach Alpha formula, and hypothesis testing uses the PLS-SEM analysis application. The research results show that transformational leadership and organizational culture positively and significantly impact lecturers' work productivity. Transformational leadership also influences organizational culture directly. Therefore, to increase lecturers' work productivity, it is necessary to improve the effectiveness of transformational leadership and organizational culture. The implications of this research highlight the importance of developing transformational leadership and organizational culture as a strategy to increase the work productivity of lecturers at the Laa Roiba Bogor National Islamic Institute.